Humanized Biomimetic Nanovesicles for Neuron Targeting (Adv. Sci. 19/2021). Issue 19 (8th October 2021) - Zinger, Assaf; Cvetkovic, Caroline; Sushnitha, Manuela; Naoi, Tomoyuki; Baudo, Gherardo; Anderson, Morgan; Shetty, Arya; Basu, Nupur; Covello, Jennifer; Tasciotti, Ennio; Amit, Moran; Xie, Tongxin; et al.
Abstract : Humanized Biomimetic Nanovesicles In article number 2101437, Assaf Zinger, Francesca Taraballi, Robert Krencik, and co‐workers optimize and validate the scalable production of neuron‐targeting biomimetic nanovesicles (NV) with distinct lipid backbones suited to potential therapeutic cargo by integrating membrane proteins from human pluripotent stem cell‐derived neurons. NVs with neuronderived membrane proteins exhibit enhanced neuronal association and uptake compared to bare NVs. These customizable NVs enable next‐generation functionalized theranostics for neurodegeneration.